Aspiration of a Blister Pack Tablet with Tracheal Obstruction and Perforation: Emergency Tracheal Repair with Extracorporeal Membrane Oxygenation Support - Schweigert, Michael; Parschke, Patrick; Almeida, Ana Beatriz; Kellner, Patrick (The Thoracic and Cardiovascular Surgeon Reports, 2023)
Background Airway management in case of acute tracheal injury is a challenging situation where the use of Extracorporeal Membrane Oxygenation (ECMO) has recently gained more importance.Case Description We report the case of a 60-year old women with aspiration of a large blister pack tablet causing acute tracheal obstruction with asphyxia as well as tracheal perforation with tension pneumothorax. As bronchoscopy failed to retrieve the blister pack, emergency tracheal reconstruction with Extracorporeal Membrane Oxygenation (ECMO) support was carried out.Conclusion The application of ECMO instantly alleviated the acute situation and provided excellent conditions for technically demanding emergency tracheal repair.
Keywords: airway; thoracic Surgery; extracorporeal membrane oxygenation